2009
DOI: 10.1089/cap.2009.0034
|View full text |Cite
|
Sign up to set email alerts
|

Early Repolarization in Young Children with Attention-Deficit/Hyperactivity Disorder Versus Normal Controls: A Retrospective Preliminary Chart Review Study

Abstract: The rate of ER in children with ADHD is significantly higher than in normal controls. Its clinical significance awaits further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
1
11
2
1
Order By: Relevance
“…Our results are applicable to a mostly minority vulnerable young urban population with ADHD who had an ECG done for cardiac screening purposes. The overall prevalence of ERPA in our ADHD patients (30.5%) suggest that our study group had similar results to those reported by Nahshoni et al 6 (32%) in Israel. They reported that a small group of children with ADHD (n = 50) had significantly higher proportion of early repolarization (ST elevation) when compared with apparently healthy control subjects (32% vs 13%, P = .012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are applicable to a mostly minority vulnerable young urban population with ADHD who had an ECG done for cardiac screening purposes. The overall prevalence of ERPA in our ADHD patients (30.5%) suggest that our study group had similar results to those reported by Nahshoni et al 6 (32%) in Israel. They reported that a small group of children with ADHD (n = 50) had significantly higher proportion of early repolarization (ST elevation) when compared with apparently healthy control subjects (32% vs 13%, P = .012).…”
Section: Discussionsupporting
confidence: 91%
“…We could find only one study that suggested that ERPA is associated with ADHD. After analyzing the electrocardiogram (ECG) tracings in a small sample of children (n = 50), Nahshoni et al 6 suggested that “the rates of early repolarization (ER) in children with ADHD is significantly higher than in normal controls (32% vs 13%, P = .012).” Our study had 2 aims: first, to determine if ERPAs were more likely present among children and adolescents diagnosed with ADHD when compared with non-ADHD children of similar demographic backgrounds. Second, to asses if children and adolescents with ADHD whose parents report severe attention difficulties and/or hyperactivity/impulsivity or “significant worry regarding their child behavior” (Parental Worry) are more likely to have ERPAs in their surface ECG when compared with other ADHD patients with mild to moderate dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…during sleep or after meals. An association with pathological conditions of autonomic imbalance, including spinal cord injuries [5] and attention deficit/hyperactivity disorder [6] , is also reported. Recent investigations found an elevated risk of malignant ventricular arrhythmia [4] , and in a community-based study the risk of death from any cause was significantly increased in subjects with ER 1 0.2 mV in the inferior leads [7] .…”
Section: Discussionmentioning
confidence: 90%
“…The copyright holder for this preprint this version posted July 17, 2020. ; https://doi.org/10.1101/2020.07.16.20155838 doi: medRxiv preprint 5 sudden cardiac death [11,12]. Recently, it has been reported that there are associations between ERP and attention-deficit hyperactivity disorder [13,14],and the patients with suicidal risks [15].…”
Section: Introductionmentioning
confidence: 99%